2019
DOI: 10.3390/cells8080842
|View full text |Cite
|
Sign up to set email alerts
|

Lasting DNA Damage and Aberrant DNA Repair Gene Expression Profile Are Associated with Post-Chronic Cadmium Exposure in Human Bronchial Epithelial Cells

Abstract: Cadmium (Cd) is a widespread environmental pollutant and carcinogen. Although the exact mechanisms of Cd-induced carcinogenesis remain unclear, previous acute/chronic Cd exposure studies have shown that Cd exerts its cytotoxic and carcinogenic effects through multiple mechanisms, including interference with the DNA repair system. However, the effects of post-chronic Cd exposure remain unknown. Here, we establish a unique post-chronic Cd-exposed human lung cell model (the “CR0” cells) and investigate the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…To dissect the molecular mechanism of TOLLIP-mediated protection, we further analyzed the changes of apoptosis markers in a lung epithelial cell line, BEAS-2B, a widely used cell line for mechanistic studies of genes related to lung diseases. [39][40][41][42] Overexpression of the TOLLIP-V5 protein in BEAS-2B cells resulted in a time-dependent decrease of bleomycin-induced caspase-3 protein cleavage up to 12 hours ( Figure 3C,E). This effect was diminished at 16 hours when the TOLLIP-V5 expression was noticeably reduced.…”
Section: Tollip Protects Bronchial Epithelial Cells From Bleomycin-mentioning
confidence: 99%
“…To dissect the molecular mechanism of TOLLIP-mediated protection, we further analyzed the changes of apoptosis markers in a lung epithelial cell line, BEAS-2B, a widely used cell line for mechanistic studies of genes related to lung diseases. [39][40][41][42] Overexpression of the TOLLIP-V5 protein in BEAS-2B cells resulted in a time-dependent decrease of bleomycin-induced caspase-3 protein cleavage up to 12 hours ( Figure 3C,E). This effect was diminished at 16 hours when the TOLLIP-V5 expression was noticeably reduced.…”
Section: Tollip Protects Bronchial Epithelial Cells From Bleomycin-mentioning
confidence: 99%
“…A, ACE2 expression data of 41 types of cancers obtained from The Cancer Genome Atlas (TCGA) database 104 ; mRNA expression z-score threshold was set at ±1.5. B, ACE2 expression in lung cancer patients with different smoking histories analyzed using similar methods as described previously 106 other symptoms in addition to respiratory symptoms, suggesting that SARS-CoV-2 could perhaps infect other organs (Figure 3). SARS-CoV-2 might infect other ACE2-expressing tissues via blood circulation as a recent report showed that SARS-CoV-2 RNA had been detected in the blood of some COVID-19 patients.…”
Section: Ace2 Expression and Covid-19 Susceptibilitymentioning
confidence: 94%
“…Indeed, increased risk of COVID-19 and poorer prognosis was observed in cancer patients. 105 In addition, using similar methods as described previously, 106 we compared the ACE2 expression in lung cancer patients of various smoking statuses.…”
Section: Ace2 Expression and Covid-19 Susceptibilitymentioning
confidence: 99%
“…Cell growth was determined by 3-(4,5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfophenyl)-2H-tetrazolium (MTS) assay according to the manufacturer’s protocol (Promega, Madison, WA, USA) and as described previously [ 26 ]. Briefly, the cells were seeded in 96-well plates at 1000 cells per well, and MTS assay was performed in a 12 h interval for up to 60 h.…”
Section: Methodsmentioning
confidence: 99%
“…Real-time quantitative PCR (RT-qPCR) was performed in order to examine the gene expression level of coilin using an ABI7500 Real-Time PCR System (Applied Biosystems, Foster City, CA, USA), and calculated using the comparative C T method as described previously [26]. Primers used are listed in Table S1.…”
Section: Gene Expression Examinationmentioning
confidence: 99%